APPLYING MURDER TECHNIQUE TO IMPROVE STUDENTSâ€™ READING COMPREHENSION OF THE SEVENTH GRADE STUDENTS OF SMP SANTO THOMAS 1 MEDAN IN THE ACADEMIC YEAR OF 2020/2021 - Pandiangan, Siska Ria; Sinaga, Anna Stasya Prima Sari; Ginting, Fiber Yun A. (Kairos English Language Teaching Journal, 2021)
The aim of this study is to find whetever Murder technique works effectively on improving studentsâ€™ reading comprehension and to describe the studentsâ€™ responses towards the application of Murder technique in the learning teaching processes of reading comprehension. The subject of the study in the seventh grade students of SMP Santo Thomas 1 Medan in the Academic Year of 2020/2021 consisting 32 students of class VII-A. This studyÂ was conducted by applying Classroom Action Research (henceforth CAR). The result of the test showed that the studentsâ€™Â meanÂ score in pre-test is 55,00Â with 16% of students got â‰¥ 70, in formative test is 68,13 with 38% of students got score â‰¥ 70, and 83,13 in post testÂ with 100% of students got score â‰¥ 70. The qualitative data analysis showed that the studentsâ€™ responses after being taught by using Murder Technique are very good. The percentage students who strongly agree is 26 (81%), agree is 27 (84%), there is no students choose strongly disagree and disagree. It is suggested that the English teachers use Murder Technique as an alternative technique in teaching reading to the students in Junior High School in order to improve their studentsâ€™ reading comprehension.